The odd one out : a spotting book - Teckentrup, Britta (Big Picture Press, an imprint of Candlewick Press, 2014)
Which bird has caught the worm? Where is the queasy monkey? And can you spot the scaredy-cat? Never has a search-and-find game been so pleasing to the eye. Each spread features fun rhyming couplets, beautiful and complexly patterned artwork, and a hidden surprise.